Nurses' perceptions of the impact of Team-Based Learning participation on learning style, team behaviours and clinical performance: An exploration of written reflections. (May 2017) - Oldland, Elizabeth; Currey, Judy; Considine, Julie; Allen, Josh
Abstract: Team-Based Learning (TBL) is a teaching strategy designed to promote problem solving, critical thinking and effective teamwork and communication skills; attributes essential for safe healthcare. The aim was to explore postgraduate student perceptions of the role of TBL in shaping learning style, team skills, and professional and clinical behaviours. An exploratory descriptive approach was selected. Critical care students were invited to provide consent for the use for research purposes of written reflections submitted for course work requirements. Reflections of whether and how TBL influenced their learning style, teamwork skills and professional behaviours during classroom learning and clinical practice were analysed for content and themes. Of 174 students, 159 participated. Analysis revealed three themes: Deep Learning, the adaptations students made to their learning that resulted in mastery of specialist knowledge; Confidence, in knowledge, problem solving and rationales for practice decisions; and Professional and Clinical Behaviours, including positive changes in their interactions with colleagues and patients described as patient advocacy, multidisciplinary communication skills and peer mentorship. TBL facilitated a virtuous cycle of feedback encouraging deep learning that increased confidence. Increased confidence improved deep learning that, in turn, led to the development of professional and clinical behaviours characteristic of high quality practice. Highlights: Team-Based Learning develops active learning styles and positive professional behaviours. Develops deep learning, increasing confidence. Expressed as improved patient advocacy and multidisciplinary communication skills. Supports development of knowledge, skills and behaviours for quality healthcare.